First Global Images of Ion Energization in the Terrestrial Foreshock by the Interstellar Boundary Explorer. Issue 16 (12th August 2020) - Dayeh, M. A.; Szalay, J. R.; Ogasawara, K.; Fuselier, S. A.; McComas, D. J.; Funsten, H. O.; Petrinec, S. M.; Schwadron, N. A.; Zirnstein, E. J.
Abstract: The Interstellar Boundary Explorer (IBEX) mission provides global energetic neutral atom (ENA) observations from the heliosphere and the Earth's magnetosphere, including spatial, temporal, and energy information. IBEX views the magnetosphere from the sides and almost always perpendicular to noon‐midnight plane. We report the first ENA images of the energization process in the Earth's ion foreshock and magnetosheath regions. We show ENA flux and spectral images of the dayside magnetosphere with significant energization of ENA plasma sources (above 2.7 keV) in the region magnetically connected to the Earth's bow shock (BS) in its quasi‐parallel configuration of the interplanetary magnetic field (IMF). We also show that the ion energization increases gradually with decreasing IMF‐BS angle, suggesting more efficient suprathermal ion acceleration deeper in the quasi‐parallel foreshock. Plain Language Summary: The Earth's bow shock occurs because the Earth's protective magnetic field, the magnetosphere, is in a supersonic flow, the solar wind from the Sun. Ahead of the bow shock is a region known as the foreshock and is created by the interplay between the interplanetary magnetic field, the solar wind, and the curvature of the bow shock. The foreshock comprises complex particle interactions and electromagnetic waves that affect the geospace environment and often perturb the magnetosphere. Our study provides the first‐ever images of ion energization in the foreshock on a global scale obtained by remote sensing. Furthermore, the measurement method enabled us to compare and quantify the energetics of the adjacent regions on both sides of the bow shock on a global scale and provide a scheme of how particles are accelerated in these regions over the entire bow shock curvature. Key Points: We present the first remote‐sensing global images of ion energization in the Earth's foreshock We provide ion energization profile as a function of bow shock obliquity We quantify the difference of energization in magnetosheath and its magnetically connected counterpart in the upstream foreshock